Eﬀective commercial activity of a company factors in digital economy - S. V. Vandysheva; A. L. Boykova (Вестник университета)
In modern world, digital economy affects all aspects of commercial activity, and successful application of digital innovations is becoming a key factor in companies’ competitiveness. Commercial organizations in their activities use software tools and the Internet, which signiﬁcantly expands their opportunities for successful development. The key factors of effective commercial activity in the context of the rapid development of digital economy have been highlighted. Referring to the statistical data of the Federal State Statistics Service, the authors analyzed the trends in information technologies implementation in Russian economy. Special attention has been paid to reviewing the main difﬁculties that Russian companies face when trying to integrate modern digital solutions into their operations. Recommendations have been given on digitalization of key components of commercial activities, including customer services automation, e-commerce, digital supply chain management, big data analytics to optimize business strategies, and online marketing. The study is supported by the examples of speciﬁc tools and techniques that have already shown their effectiveness in practice for Russian companies adapting to digital economy. The research is based on the system and process approaches.